Loan Loss Provision and Pro-cyclicality: Evidence from Chinese Banks - Xue, Dongmei (2011)
This study is to investigate how Chinese bank provisioning behaviour is related to business cycle using a GMM for 619 bank-year observations from 2003 to 2010. Loan loss provisioning is heavily dependent upon the performance of the real economy. Provisioning turns out to be substantially lower when real GDP growth rate is higher and asset price is rising, suggesting increased risks of loan portfolio in economic downswing. The pro-cyclicality of provision behaviour is also exacerbated by the fact that banks provision less when loan growth is strong and regulatory capital ratio is negatively correlated with provisioning, suggesting capital management via loan loss provision. This effect is mitigated by earning management, where provision rise when earnings are positively higher. When examining the ownership effect on banks’ provision behaviour, state banks provision more than non-state banks when credit risks increase, suggesting more prudent provisioning behaviour.